NEEDS OVER RIGHTS: THE RIGHT TO HEALTH IN STATE SOCIALIST HUNGARY AND ITS IMPLEMENTATION - Varju, Marton; Sándor, Judit (Pravni zapisi, 2024)
State socialist Hungary undertook historically unparalleled action to sat- isfy the health needs of its population. To support its efforts, it recognized in its constitution the protection of health as an essential state task and, later, a right to health. Although formulated as a right of citizens, the right to health was not available to enfranchise the individual. Instead, it expressed common social needs, as well as the responsibility and the institutional obligation of the socialist state to take care of those needs. This emphasis on needs over individual rights had a crucial impact on the implementation of the right to health. Contemporary and retrospective policy and sociological analyses reveal that the healthcare system in state socialist Hungary left the individual exposed to institutional and professional interests within the health system, and their vulnerability as a patient was regularly exploited.
Keywords: Socialist Fundamental Rights; Right to Health; State Socialism; Socialist Healthcare; Vulnerability